FISCAL AND SOCIAL DETERMINANTS OF PERSONAL INCOME TAXATION - UHRYN, Volodymyr (Scientific journal «World of Finance», 2021)
Introduction. Direct taxes are an important financial regulator of socio-economic processes, they are one of the most important sources of budgeting and an essential tool of state regulation. The personal income tax is the main tax through which social policy is implemented in the developed countries of the world. The advantages of this tax include its social justice and fiscal efficiency, as it is able to make the level of taxation directly dependent on the amount of income of taxpayers. In addition, progressive tax rates and benefits can reduce the tax burden on the poor and increase it on high-income earners.The purpose of the article is to considerate the theoretical and practical aspects of administration of the personal income tax in the conditions of reforming of fiscal policy of Ukraine, systematization of directions of improvement of collecting of the personal income tax to local and state budgets.Methods. Methods of dialectical analysis and synthesis, deduction, induction logical generalization, comparison and formalization are used in the article.Results. The article is devoted to the study of the essence and role of personal income tax administration. Peculiarities of citizens’ income formation as an object of taxation are considered. Monitoring and analysis of indicators of personal income tax to local and state budgets was carried out. The growth rates of nominal revenues of personal income tax and military duty, real and nominal wages are studied. It was found that the main factors reducing the level of fiscal efficiency of personal income tax in Ukraine are the shadowing of incomes and the outflow of labor, including skilled personnel. Ukraine’s tax policy for the last five years is fiscally oriented and does not take into account the social aspect of personal income taxation. As a result of the research, the directions of increasing the efficiency of personal income taxation in Ukraine based on foreign experience are systematized.Prospects. The current model of personal income tax does not sufficiently perform a socioeconomic function, does not provide a socially equitable distribution of income between different segments of the population. In recent years, the fiscal significance of the personal income tax has remained, but the system of personal income taxation requires the application of progressive rates. Therefore, promising areas of future research should be the development and improvement of the mechanism of personal income taxation in the context of ensuring their socio-economic interests.